Practitioner requirements for integrated Knowledge-Based Engineering in Product Lifecycle Management. - Bermell-Garcia, Pablo; Fan, Ip-Shing (Cranfield University, 2008)
The effective management of knowledge as capital is considered essential to the success of engineering product/service systems. As Knowledge Management (KM) and Product Lifecycle Management (PLM) practice gain industrial adoption, the question of functional overlaps between both the approaches becomes evident. This article explores the interoperability between PLM and Knowledge-Based Engineering (KBE) as a strategy for engineering KM. The opinion of key KBE/PLM practitioners are systematically captured and analysed. A set of ranked business functionalities to be fulfiled by the KBE/PLM systems integration is elicited. The article provides insights for the researchers and the practitioners playing both the user and development roles on the future needs for knowledge systems based on PLM.
Keywords: computer aided design; CAD; engineering design; engineering knowledge management; knowledge-based engineering; KBE; product lifecycle management; PLM